Finite element analysis of bone‐prosthesis interface micromotion for cementless talar component fixation through critical loading conditions. (28th January 2020) - Moideen, Irwan S.M.; Lim, Chin Tat; Yeow, Raye C.H.; Chong, Desmond Y.R.
Abstract: The total ankle replacement (TAR) survivability rate is still suboptimal, and this leads to many orthopaedic surgeons opting arthrodesis as a better option for the ankle arthritis patients. One of the fundamental reasons is due to the lack of primary stability of the prosthesis fixation at the bone‐prosthesis interface hence leading to long‐term aseptic loosening of the talar component. The commercially available Scandinavian Total Ankle Replacement (STAR) Ankle design and several additional design features (including trabecular metal, side fin, double fin, and polka‐dot designs) were studied using finite element analysis, and the bone‐prosthesis interface relative micromotion (BPIRM) and talar bone minimum principal stresses were examined and analysed. Three loading conditions at a gait cycle of heel strike, midstance, and toe off with different meniscal bearing displacement were also included as part of the study parameters. The results were correlated to in vitro cadaveric measurements and reported clinical studies. Simulated results showed that the de‐bonding relative distance between the bone and prosthesis upon loading (COPEN defined by the simulation software) was the main reason constituting to the high interface micromotion between the talar component and talus bone (which could lead to long‐term aseptic loosening). The polka‐dot design was shown to induce the lowest BPIRM among all the designs studied. Abstract : Primary stability of the talar component upon implantation is important in preventing the overall total ankle replacement (TAR) aseptic loosening failure. Thus, this study will include the commercial TAR of STAR (Scandinavian Total Ankle Replacement) Ankle to investigate the failure mechanism of the talar component when subjected to physiological loading. Different design features (trabecular metal [TM], side fin [SF], double fin [DF], and polka dot [PD]) and its influence were also evaluated and compared with the commercial STAR Ankle talar component through finite element analysis (FEA). Different critical loading conditions consisting the heel strike, midstance, and toe‐off of a human walking gait cycle were prescribed to the FEA models. The FEA predicted results were validated through clinical outcome results and experimental cadaveric studies. Predicted FEA results through contour plots have shown that (a) high bone‐prosthesis relative interface micromotion (BPRIM) of the STAR Ankle was mainly due to the de‐bonding displacement, (b) this was significantly concentrated on posterior regions of interest, and (c) PD design was predicted to address the primary stability. In validating the FEA models, the experimental and predicted max/min principal bone strains were fitted into regression models and showed good correlations for the STAR Ankle ( R 2 of .858) and polka dot ( R 2 of .812) designs, respectively. In conclusion, the PD talar component design was found to be a favourable design with reduced BPRIM thereby potentially increasing the primary stability and reducing the risk of long‐term aseptic loosening.